Artificial intelligence and machine learning for business : a no-nonsense guide to data drive technologies - Finlay, Steven, ....- (S.l. : Relativistic, 2017)
Artificial Intelligence (AI) and Machine Learning are now mainstream business tools. They are being applied across many industries to increase profits, reduce costs, save lives and improve customer experiences. Consequently, organisations which understand these tools and know how to use them are benefiting at the expense of their rivals. Artificial Intelligence and Machine Learning for Business cuts through the technical jargon that is often associated with these subjects. It delivers a simple and concise introduction for managers and business people. The focus is very much on practical application, and how to work with technical specialists (data scientists) to maximise the benefits of these technologies.
Keywords: Technologie